The POTENTIAL OF LACTIC ACID BACTERIA, ISOLATED FROM SEVERAL SOURCES, TO INHIBIT THE GROWTH OF Candida albicans ATCC10231 - Yan Ramona; Ida Bagus Gede Darmayasa; Komang Dharmawan; Putu Eka Sudaryatma; Ni Made Teriyani; Yanuarius Felix Batho; Fainmarinat Selviani Inabuy (BIOTROPIA, 2024)
ARTICLE HIGHLIGHTS- Lactic acid bacteria have potential to control candidiasis or Candida albicans. - The novelty of this study is to advance the potential of lactic acid bacteria to control candidiasis infection in human, with a view to develop novel LAB-based probiotic candidates with capability to inhibit/prevent infection by C. albicans, the causative agent of candidiasis.ABSTRACTThe main aims of this research were to isolate and identify potential lactic acid bacteria (LAB) inhibitory to Candida albicans. The LAB sources were kimchi, honey and vaginal secrete of healthy women. They were isolated with a view to develop a novel alternative method with reduced use of antifungal agents in the treatment of patients infected by such fungal pathogen. Isolation of the LABs was conducted by applying dilution spread method on de Mann Rogosa Sharpe agar (MRSA) medium supplemented with bromo cresol purple (BCP) indicator. Once purified, they were tested for antagonism against C. albicans in dual culture assays. LAB isolates that showed significant inhibition against the pathogen were identified using 16s rDNA sequences and their sequences were aligned with those of known sequences deposited at the Gene Bank (http://www.ncbi.nlm.nih.gov). The results showed that 46 among more than 100 LABs isolated in this study significantly inhibited the growth of C. albicans in the in vitro dual culture assays, and all showed resistance property to antifungal agent (fluconazole). This indicated that they all have potential to be synergically applied with reduced use of fluconazole in the therapy. The most potential isolates (10 isolates) were closely related to three LAB species, namely Lactobacillus paracasei, Lacticaseibacillus paracasei, and Pediococcus pentosaceus, based on their 16s rDNA sequence similarities with those deposited in the GenBank.